State Taxation of Nonresident Income and the Location of Work - David R. Agrawal; Kenneth Tester (Global Labor Organization (GLO), 2023)
Prior studies show that taxes matter for the residential locations of high-income earners. But, states raise a significant share of revenue from nonresidents. Using variation in state tax rates, we provide causal evidence on the effect of the net-of-tax rate on the location of labor supply for professional golfers. State taxes induce high-income earners to shift employment to low-tax states without a residence change. The elasticity of working in a state is 0.34, and consistent with superstar phenomenon, increases with earnings. Our results suggest a novel margin of mobility responses for top-earners: the spatial relocation of labor supply by nonresidents.
Keywords: J22; J61; H26; H73; R50; 330; state taxes; superstars; taxing the rich; avoidance; mobility; highfrequency labor supply